Conventional and Non-Conventional Targets of Natural Products in the Management of Diabetes Mellitus and Associated Complications - Mahomoodally, Mohamad F.; Lobine, Devina; Picot-Allain, Marie C. N.; Sadeer, Nabeelah; Jugreet, Sharmeen; Zengin, Gokhan (Current Medicinal Chemistry, 2021)
Background: Diabetes Mellitus (DM) is a severe endocrine metabolic disease coupled with various long-term complications. A plethora of targets have been identified, however, with possible adverse effects. Therefore, researchers are in the perpetual quest for safe and more effective therapeutics. Natural products, particularly derived from plants, have proven to exert anti-diabetic effects via diverse mechanisms. Methods: An overview of DM pathogenesis and its associated micro- and macro-vascular complications is presented. Possible underlying mechanisms of herbal remedies in DM management are provided, highlighting some key therapeutic targets. The review also appraises the recent progress of herbal products in treating DM through regulating inflammation and gut microbiota. Finally, currently available pharmacological treatments are discussed. Results: The results show that numerous plants have proven to be promising sources of insulin secreting agents, α-glucosidase and α-amylase inhibitors. Among the non- conventional targets, inhibition of key enzymes such as lipase, cholinesterases and angiotensin converting enzyme has been directly and/or indirectly linked to DM and DM complications. For instance, hypericin, pseudohypericin and I3,II8-biapigenin isolated from Hypericum perforatum L., and palmatine and columbamine isolated from Dichocarpum auriculatum (Franch.) W. T. Wang & P. K have been found to be powerful lipase and cholinesterase inhibitors, respectively. Moreover, a number of plant-derived compounds such as feruloylated oligosaccharides from maize bran, baicalein and berberine are reported to mediate anti-diabetic property via modulation of gut microbiota. Conclusion: The information amassed in this review is anticipated to provide useful scientific baseline information to support advanced research in natural antidiabetic drug development.
Keywords: drug